A skin disease and needs assessment analysis of the displaced Rohingya population in the Kutupalong refugee camp, Bangladesh. (29th July 2020) - Khan, S. S.; Padovese, V.; Maurer, T. A.; Barua, D. P.; Chowdhury, M. I. H.; Islam, M. A.; Mowla, M. R.; Griffiths, C. E. M.
Summary: The physical, psychological and financial burden of skin disease in low‐ to middle‐income countries, where access to skincare is limited, is poorly understood. A group that we know very little about in this regard are refugees. There are limited data on the range of skin diseases and skincare needs of this group. To better understand the skincare needs of the displaced Rohingya population residing in the Kutupalong refugee camp, Bangladesh, we collected data on demographics, living conditions and range of dermatoses. In the 380 patients assessed, fungal skin infections, predominantly dermatophytes, were by far the most common skin disease seen ( n = 215), followed by dermatitis ( n = 81). Skin disease can be the presenting feature in many systemic conditions and may cause significant secondary complications itself. Developing a better understanding of the skincare needs of the refugee population is essential for future healthcare planning for this vulnerable group.